Effectiveness of safe child birth checklist on maternal and perinatal outcomes in tertiary level hospitals - Varaganti, Neelima; Sangabathula, Himabindu; Guthi, Visweswara Rao (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The World Health Organization (WHO) estimates nearly 2,87,000 maternal deaths, 1 million intrapartum related stillbirths and another 3 million new born deaths during the neonatal period against more than 130 million births each year. Intrapartum perinatal mortality, the deaths that occur during the period around birth, is a major problem in developing countries Objective of this study is to study the effectiveness of safe child birth checklist on maternal and perinatal outcomes in tertiary level hospitals. Methods: This study is a hospital based prospective interventional study conducted at MGMH, Petlaburzu hospital, Hyderabad, Telanagana, which is a tertiary care hospital comes under Osmania medical college. 635 deliveries were followe up without SCC and 620 deliveries were followed up with SCC. Results: There was significant improvement in starting of partograph at the time of admission with SCC (20% vs 32.2%), more number of cases required to start antibiotics in with SCC group compared to without SCC. Just Before and during Birth (or C-Section) without SCC group significantly more need to start Antibiotic compared to with SCC group (15.7% vs 11.3%) and active management of third stage of labour was significantly more among with SCC group (94.5% vs 96.9%). Conclusions: In final mortality and morbidity outcomes of delivery i.e. maternal and perinatal, the effectiveness of implementation of safe child birth check list has no significant effect though there were improved set of certain practices during the child birth process.